Ask a New Question
Search
Which of the following correctly demonstrates the use of the
Which example correctly demonstrates polynomial subtraction?
A. (2x^2 + 6x + 1) – (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B. (2x^2 +
1 answer
19 views
Which example correctly demonstrates polynomial addition?
A. (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B. (2x^2 + 6x +
3 answers
20 views
Which example correctly demonstrates polynomial subtraction?
(2x2+6x+1)−(3x2+3x+9)=x2+3x+8 (2x2+6x+1)−(3x2+3x+9)=5x2+9x+10
1 answer
14 views
Which of the following correctly demonstrates the commutative property
1 answer
6 views
Which example correctly demonstrates polynomial subtraction?
A) (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = x^2 + 3x + 8 B) (2x^2 + 6x +
1 answer
56 views
Which example correctly demonstrates polynomial subtraction?
(2x2+6x+1)−(3x2+3x+9)=5x2+9x+10
1 answer
21 views
Which example correctly demonstrates polynomial subtraction? (2x2+6x+1)−(3x2+3x+9)=x2+3x+8
(2x2+6x+1)−(3x2+3x+9)=5x2+9x+10
1 answer
15 views
Which example correctly demonstrates polynomial addition
1 answer
28 views
which example correctly demonstrates polynomial addition
(2x^2+6x+1)+(3x^2+3x+9)=-x^2+3x-8 (2x^2+6x+1)+(3x^2+3x+9)=5x^2+9x+10
1 answer
asked by
lol
13 views
Which example correctly demonstrates polynomial addition?
A) (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B) (2x^2 + 6x +
1 answer
14 views